MENINGKATKAN MINAT BELAJAR ANAK-ANAK PANTI SELAMA PANDEMI COVID19 BERSAMA MAHASISWI KESEJAHTERAAN SOSIAL FISIP USU - Sriulina Ginting (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
The author conducted practicum II at the Delpita Talent Orphanage. The second practice carried out by the author is to examine the problems experienced by orphanage children. The problem experienced by orphanage children is the lack of understanding in the online learning process during the COVID-19 pandemic so that they feel bored and lose interest in learning. From these problems, the author is interested and has the goal to increase the interest in learning of orphanage children and the author makes this goal as a mini project. The author has a client who is experiencing problems, the client consists of children who are still in elementary school. The author uses the general stages in his research, ranging from the preparatory stage to the termination stage. The author also uses the delphi method by using Focus Group Discussion (FGD) with the aim that the discussion goes according to plan. After doing all the general stages, the author hopes that the children of the orphanage can return to studying hard.